Transcutaneous Vagus Nerve Stimulation (tVNS) applications in cognitive aging: a review and commentary - Naparstek, Sharon; Yeh, Ashley K.; Mills-Finnerty, Colleen (Frontiers in Aging Neuroscience, 2023)
Differentiating healthy from pathological aging trajectories is extremely timely, as the global population faces an inversion where older adults will soon outnumber younger 5:1 (World Health Organization, 2022). Many cognitive functions (e.g., memory, executive functions, processing speed) decline with age, a process that can begin as early as midlife, and which predicts subsequent diagnosis with dementia. Although dementia is a devastating and costly diagnosis, there remains limited evidence for medications, therapies, and devices that improve cognition or attenuate the transition into dementia.There is an urgent need to intervene early in neurodegenerative processes leading to dementia (e.g., depression, mild cognitive impairment).In this targeted review and commentary, we highlight transcutaneous Vagus Nerve Stimulation (tVNS) as a neurostimulation method with unique opportunities for applications in diseases of aging, reviewing recent literature, feasibility of use with remote data collection methods/telehealth, as well as limitations and conflicts in the literature. In particular, small sample sizes, uneven age distributions of participants, lack of standardized protocols, and oversampling of non-representative groups (e.g., older adults with no comorbid diagnoses) limit our understanding of the potential of this method. We offer recommendations for how to improve representativeness, statistical power, and generalizability of tVNS research by integrating remote data collection techniques.